Enhancing Argumentative Essay Writing Skills in Junior High School Students through Mind Mapping - Lalo Daeng; Fransiska Enre (International Journal of Curriculum Development, Teaching and Learning Innovation, 2024)
This research investigates the efficacy of integrating mind mapping into the writing curriculum for junior high school students to enhance argumentative essay writing skills. Grounded in principles of student-centered learning and cognitive psychology, the study adopts a quasi-experimental design to compare the outcomes of students exposed to mind mapping with those receiving traditional writing instruction. Quantitative analyses of pre-test and post-test scores reveal significant improvements in argumentative essay writing proficiency among students in the intervention group, indicating the effectiveness of mind mapping in facilitating the organization and synthesis of ideas. Additionally, qualitative analyses highlight positive shifts in students' attitudes towards writing and enhanced critical thinking abilities following exposure to mind mapping instruction. These findings underscore the transformative potential of mind mapping as a pedagogical tool for fostering student engagement, creativity, and academic achievement in the digital age. The implications for teaching practices and curriculum development in junior high schools are discussed, emphasizing the importance of leveraging innovative instructional approaches to meet the diverse needs and learning styles of students. Overall, this research contributes valuable insights to the ongoing discourse on writing instruction and underscores the significance of integrating technology-rich learning experiences to empower students as effective communicators and critical thinkers in the 21st century.